2005
DOI: 10.1016/j.molcel.2004.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Dynamic Kinetochore- Microtubule Interface through Assembly of the Dam1 Ring Complex

Abstract: How kinetochore proteins form a dynamic interface with microtubules is largely unknown. In budding yeast, the 10-protein Dam1 complex is an Aurora kinase target that plays essential roles maintaining the integrity of the mitotic spindle and regulating interactions with the kinetochore. Here, we investigated the biochemical properties of purified Dam1 complex. The complex oligomerized into rings around microtubules. Ring formation was facilitated by microtubules but could occur in their absence. Mutant alleles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
408
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(437 citation statements)
references
References 35 publications
27
408
1
1
Order By: Relevance
“…In addition, the DASH complex is localized at the kinetochore and the spindle and is required for spindle attachment to the kinetochore (Cheeseman et al, 2001;Li et al, 2002). The S. cerevisiae DASH complex is composed of 10 proteins that localize at the kinetochore and the spindle (Miranda et al, 2005;Westermann et al, 2005). Biochemical analyses have revealed that the kinetochore complex is comprised of subcomplexes of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the DASH complex is localized at the kinetochore and the spindle and is required for spindle attachment to the kinetochore (Cheeseman et al, 2001;Li et al, 2002). The S. cerevisiae DASH complex is composed of 10 proteins that localize at the kinetochore and the spindle (Miranda et al, 2005;Westermann et al, 2005). Biochemical analyses have revealed that the kinetochore complex is comprised of subcomplexes of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, we relied on a motility assay using the Dam1 complex 11 (also known as DASH, or DDD), a putative load-bearing component of kinetochores in yeast [11][12][13][14]26 . Like kinetochores, pure recombinant Dam1 complex forms robust connections to growing and shortening MT tips that remain attached even when tension is applied 14 .…”
mentioning
confidence: 99%
“…Another important candidate found in budding yeast was the Dam1 complex, which can form rings around microtubules in vitro [129].…”
Section: Force Generation By Microtubule Depolymerization From Plus-endsmentioning
confidence: 99%